(untitled) (Bioresearch Communications, 2024)
Seventeen microsatellite loci from the non-recombining region of the human Y chromosome were typed using AmpFlSTR® Yfiler® PCR amplification systems in 404 male subjects belonging to the three largest ethnic groups in Bangladesh. A total of 150 haplotypes from the Chakma, 144 from the Tripura, and 110 from the Khasia were detected with a corresponding discrimination capacity of 73.885%, 65.563%, and 81.250%, respectively. The highest allele frequency of 0.828 was detected in DYS391 locus in the Tripuras, while the lowest allele frequency of 0.009 was detected at the same locus for the Chakma population. The highest gene diversity (0.964) was observed at DYS385a/b locus in the Khasias, while the lowest gene diversity (0.301) was detected at DYS391 locus in Tripuras population. The overall haplotype diversity for the studied populations was 0.986141. Both the Neighbour-Joining tree and pairwise genetic distances showed that Chakma lies closer to a clade consisting of Tripuras (Khagrachari, Bangladesh) and Tripuri (Tripura, India). In contrast, the Khasias demonstrated a close affinity with the Oraon (Chhattisgarh, India), followed by the Santals. The Y-STR haplotype matching probabilities within and between populations demonstrated that the Chakma, Tripura, and Khasia were 100% genetically distinct. The studied ethnic populations exhibited higher frequency for haplogroups L and Q as opposed to haplogroups R1a, H, and L found in the mainstream Bengali population. The Median-joining networking showed haplogroups L and R1a have the most compact clustering within populations, followed by haplogroups Q and H. The presence of haplogroup R1a suggests that Bengali may have originated through west-to-east migration, whereas haplogroups L and Q distribution in the studied tribes reveal a very significant affinity with the South-East Asian populations and may have shared a common ancestral origin with the Mongoloid stock populations. Bioresearch Commu. 10(2): 1482-1488, 2024 (July)